Pathogenesis of diarrhea in patients with COVID-19 and approaches to therapy - E. A. Lyalyukova (Лечащий Врач, 2022)
Diarrhea is observed in a significant proportion of patients with SARS-CoV-2 infection, both in the acute phase and in the post-COVID period. The purpose of the review is to present current data on the epidemiology and pathogenesis of diarrhea in patients with COVID-19, SARS-CoV-2, on therapeutic and preventive measures in patients during the acute phase and the post-COVID period. Intestinal injury associated with COVID-19 is often multifactorial and may be due to direct cytopathic effects on the gastrointestinal epithelium, immune-mediated injury, ischemic/hypoxic injury, as well as disruption of the gut microbial landscape or the development of C. difficile-associated colitis, a side effect of some drugs used to treat COVID-19. Given that one of the leading causes of diarrhea in patients with COVID 19 is the secretory genesis of diarrhea, rehydration therapy, sorbents and cytoprotectors are used in the treatment. In patients with C. difficile-associated colitis, metronidazole and vancomycin are the drugs of choice. Prevention of C. difficile-associated colitis includes the use of probiotics Saccharomyces boulardii, Lactobacillus rhamnosus and others, as well as probiotic mixtures. One of the therapeutic measures is the prevention of the development of severe toxicosis, sorption and elimination of toxic compounds from the intestines. Phytosorbents, herbal preparations (dietary fibers), the main properties of which are their solubility and fermentability by intestinal bacteria, demonstrated a high ability to enterosorption. Thanks to this polyfractional structure, psyllium has a complex effect not only on the intestines, but also on the body as a whole. The main effects of psyllium (detoxification, antidiarrheal, anti-inflammatory, cytoprotective restoration of the intestinal microbiota) make it possible to use it as a pathogenetic agent in patients with COVID-19, both in the acute phase and in the post-COVID period.